CURRENT ISSUES IN THE USE OF ANTIBIOTICS - Sharipova Matluba Tursunovna (Western European Studies, 2025)
The use of antibiotics has become a cornerstone of modern medicine, but their misuse and overuse have led to serious global health concerns. This article examines the current issues related to antibiotic use, including antibiotic resistance, overprescription, regulatory challenges, and the need for new drug development. The study incorporates a literature review, methodologies for analyzing antibiotic impact, and discussions on potential solutions to mitigate associated risks.
Keywords: Antibiotics; antibiotic resistance; overuse